STRATEGI PENGUMPULAN DAN PENDISTRIBUSIAN DANA ZAKAT BAZNAS KOTA JAMBI DALAM UPAYA PEMBERDAYAAN MASYARAKAT - Septi Susanty; As’ad Isma; Nurlia Fusfita (Lembaga Pengembangan Kinerja Dosen, 2023)
Zakat is one of the pillars of Islam which is always equated with prayer in accordance with the verse of the Qur'an Surah Al Baqarah verse 43. Zakat as a social aspect, hopes that zakat can reduce and even overcome the income gap for the rich and the poor. In addition, zakat is also expected to be able to increase or grow the economy, either at the individual level or at the social level of society in general. Zakat in the moral aspect can erode greed and greed for the rich. Whereas in the economic aspect, zakat can prevent the accumulation of wealth for a handful of people, zakat is distributed before wealth increases and is dangerous in the hands of the owner. The method used in this research is descriptive qualitative research. This research was conducted at the National Amil Zakat Agency (BAZNAS) Jambi City. This study discusses the strategy of collecting, distributing and impacting zakat funds. This is in order to increase the potential of zakat funds collected by BAZNAS Jambi City.